The Effects of Conventional Method, Mind Mapping Method, and Learning Motivation on Thematic Learning Outcomes in 3rd Grade of Elementary School - Irbawati, Wahyu Niken; Wiryokusumo, Iskandar; Leksono, Ibut Priono (International Journal of Educational Technology and Learning, 2019)
This study aims to determine the effect of mind mapping vs. conventional methods and learning motivation on learning outcomes in the thematic subjects of energy themes and changes in energy change sub-themes 2 in third grade students of SD Muhammadiyah 1 and SD Muhammadiyah 2 Waru 2017/2018 academic year. Sources of data were obtained from students of SD Muhammadiyah 1 Waru with a total of 47 students and SD Muhammadiyah 2 Waru with 38 students. This study uses experimental research design with the form of Factorial Design with the sampling technique is Cluster Sampling. The results of the study concluded that the experimental group students showed better learning outcomes compared to the control group. Students who had high learning motivation towards thematic subjects had better learning outcomes compared to students who had low learning motivation on thematic subjects, and not there is interaction between mind mapping vs. conventional methods and student learning motivation on thematic subjects in grade 3 of Muhammadiyah 1 Waru Elementary School and Muhammadiyah 2 Waru Elementary School in the academic year 2017/2018.